2012
DOI: 10.2350/12-05-1204-cr.1
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastoma: Report of a Rare Entity in the Pediatric Population

Abstract: Fibroblastic and myofibroblastic tumors constitute an important group of neoplasms in children and adolescents. These span the full spectrum of clinical behavior, ranging from benign to intermediate and malignant. We report a case of a benign mesenchymal tumor with myofibroblastic differentiation in a 9-year-old girl arising in the left groin that met the histologic features described for myofibroblastoma in adults. Two types are recognized in adults: angiomyofibroblastoma and mammary-type myofibroblastoma of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The youngest adult case of AMF-like tumour was reported by Bouhajja et al in 2017 in a 27-year-old patient [7]. Chami et al reported a case of benign mesenchymal tumour with myofibroblastic differentiation in a 9-year-old girl arising in the left groin that met the histologic features described for myofibroblastoma in adults [8]. Treatment is surgical resection with wide excision to tumour-free margins to prevent recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…The youngest adult case of AMF-like tumour was reported by Bouhajja et al in 2017 in a 27-year-old patient [7]. Chami et al reported a case of benign mesenchymal tumour with myofibroblastic differentiation in a 9-year-old girl arising in the left groin that met the histologic features described for myofibroblastoma in adults [8]. Treatment is surgical resection with wide excision to tumour-free margins to prevent recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis for extra-MTMF includes neoplasms of a benign (benign nerve sheath tumour, solitary fibrous tumour, leiomyoma, spindle cell lipoma (SCL), cellular angiofibroma, angiofibroblastoma, angiomyxoma and soft tissue perineurioma) and malignant (liposarcoma, dermatosarcoma protuberans) nature 14 17. However, extra-MTMF is most often confused with SCL since they are both composed of CD34 positive spindle cells interspersed with adipose tissue 5 17.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this patient's case, the mass was relatively encapsulated. They are typically composed of spindle-shaped cells arranged in fascicles, interspersed within a collagenous stroma 2 4 14 17–19. There is also a variable adipocytic component 2 18.…”
Section: Discussionmentioning
confidence: 99%
“…After that, superficial myofibroblastoma of the lower female genital tract was initially described in 2001 [ 2 ]. Due to the rarity of the tumor, only a few case reports or case series have been reported [ 3 4 5 ]. Recently, the wider anatomic distribution of myofibroblastoma was reported [ 6 ] and is now increasingly recognized.…”
Section: Introductionmentioning
confidence: 99%